Control of Myelination by Specific Patterns of Neural Impulses - Stevens, Beth (J Neurosci, 1998)
A cell culture preparation equipped with stimulating electrodes was used to investigate whether action potential activity can influence myelination of mouse dorsal root ganglia axons by Schwann cells. Myelination was reduced to one-third of normal by low-frequency impulse activity (0.1 Hz), but higher-frequency stimulation (1 Hz) had no effect. The number of Schwann cells and the ultrastructure of compact myelin were not affected. The frequency of stimulation that inhibited myelination decreased expression of the cell adhesion molecule L1, and stimulation under conditions that prevented the reduction in L1 blocked the effects on myelination. This link between myelination and functional activity in the axon at specific frequencies that change axonal expression of L1 could have important consequences for the structural and functional relationship of myelinating axons.